Effect of Modified Deformed Steel Fiber on Mechanical Properties of Artificial Granite - Xuetao Qiao; Peng Wang; Cunfu Yan; Fang Li; Long Wu (Advances in Civil Engineering)
In order to explore the influence of the shape and surface treatment of steel fiber on the mechanical properties of artificial granite matrix, the drawing models of W-type, L-type, V-type, and I-type steel fiber are established, the pull-out force of different shapes of steel fiber is calculated theoretically, and a large number of experimental specimens are made for the pull-out test of steel fiber and material strength test. Both theory and experiment show that W-type steel fiber has the greatest influence in artificial granite. The steel fibers with different shapes were treated with KH-550 silane coupling agent. Then the steel fibers with different shapes before and after treatment were put into the artificial granite matrix for pull-out test and material strength test. The results showed that, compared with L-type, V-type, and I-type steel fibers before and after KH-550 silane coupling agent treatment, W-type steel fibers after KH-550 silane coupling agent treatment have the best strength enhancement effect in artificial granite matrix.